The timeliness of the effects of monetary policy: the new evidence from econometric models - WHITE, W.H. (PSL Quarterly Review, 2014)
<!--[if gte mso 9]> 72 1024x768 <![endif]--> The usefulness of monetary policy for smoothing out cyclical movements or keeping the economy on its desired growth path has long been a matter of debate. In the past, monetary policy was often condemned as being ineffectual. More recently, discretionary monetary policy has been condemned on the ground that its effects would be realised with an uncertain but long delay. Most recently, a number of elaborate econometric models have shown either little or no effect in monetary policy measures or important effects which are realised only after a long lag. The present article points out some flaws and misspecifications in these studies and argues that the evidence remains in favour of the case for sufficiently short lags in the effects of monetary policy. The author concludes that not only has the lag problem in the use of monetary policy been greatly exaggerated by some econometric studies, it also appears that the lag in the alternative fiscal policy has been underestimated. JEL: E52, E62 <!--[if gte mso 9]> Normal 0 14 <![endif]--><!--[if gte mso 10]> <![endif]-->